2007
DOI: 10.1016/j.cub.2007.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with Evaluation in Ants

Abstract: Tandem running in ants is a form of recruitment in which a single well-informed worker guides a naive nestmate to a goal [1-8]. The ant Temnothorax albipennis recently satisfied a strict set of predefined criteria for teaching in nonhuman animals [9, 10]. These criteria do not include evaluation as a prerequisite for teaching [10]. However, some authors claim that true teaching is always evaluative, i.e., sensitive to the competence or quality of the pupil [11-13]. They then assume, on the premise that only hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 36 publications
3
71
0
1
Order By: Relevance
“…We argue that the interaction patterns between populations are the crucial part of the decision-making process at both these levels of biological complexity, organismal and super-organismal. Notwithstanding their impressive individual abilities (Koch 1999), neurons are simple in comparison with individually sophisticated social insects (Giurfa et al 2001;Chittka et al 2003;Franks et al 2003b;Franks & Richardson 2006;Richardson et al 2007). Simple interaction patterns in both these systems, however, may implement robust, efficient decision-making regardless of how sophisticated their individual components are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that the interaction patterns between populations are the crucial part of the decision-making process at both these levels of biological complexity, organismal and super-organismal. Notwithstanding their impressive individual abilities (Koch 1999), neurons are simple in comparison with individually sophisticated social insects (Giurfa et al 2001;Chittka et al 2003;Franks et al 2003b;Franks & Richardson 2006;Richardson et al 2007). Simple interaction patterns in both these systems, however, may implement robust, efficient decision-making regardless of how sophisticated their individual components are.…”
Section: Discussionmentioning
confidence: 99%
“…In T. albipennis, scouts recruit nest-mates to a site they have discovered by tandem running, teaching others the route (Möglich & Hölldobler 1974;Möglich 1978;Franks & Richardson 2006;Richardson et al 2007). The recruiters pause for longer before recruiting to poor nests than they do for good nests (Mallon et al 2001).…”
Section: Decision-making In Social Insect Coloniesmentioning
confidence: 99%
“…Moreover, teachers may have evolved mechanisms allowing sensitivity to current circumstances. Richardson, Houston, and Franks (2007), for example, showed that T. albipennis leaders' investment in a bout of teaching (a tandem run to or from a nest site) is responsive to the time already invested in that bout, the quality of the goal (poor or good quality nests), and the speed of the follower. Richardson et al's techniques of interrupting bouts of teaching and altering the quality of goals may be of great use in assessing the degree of sensitivity shown by teachers in other species as well.…”
Section: Teaching Promotes Learningmentioning
confidence: 99%
“…Richardson et al's techniques of interrupting bouts of teaching and altering the quality of goals may be of great use in assessing the degree of sensitivity shown by teachers in other species as well. Further manipulations, such as experimentally reducing pupils' ability to learn (e.g., Richardson et al, 2007), may also prove helpful in analyzing teaching in vertebrate species but should be given careful ethical consideration.…”
Section: Teaching Promotes Learningmentioning
confidence: 99%
“…First, in T. albipennis tandem running has a pivotal role in new nest choice (Pratt et al, 2002); such decisions are likely to influence the inclusive fitness of all colony members, so it would benefit the colony to have the most able individuals performing this task. Second, tandem running is such a sophisticated form of communication that it actually qualifies as a form of teaching (Franks and Richardson, 2006;Richardson et al, 2007). Indeed, it trains other recruiters because followers of tandem runs often become leaders of subsequent tandem runs (Möglich et al, 1974;Franks and Richardson, 2006;Richardson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%